Analisis Strategi Komunikasi Pemasaran MS Glow Kepada Konsumen Melalui Instagram dalam Meningkatkan Brand Awareness - Nirwana, Tri Ruwanti Bela; Hamidah; Muslimin (Indonesian Journal Publisher, 2024)
Communication strategies in marketing can help consumer interest which will have an impact on increasing sales and good brand awareness. The aim of this research is to find out how Ms Glow's marketing communication strategies and supporting and inhibiting factors to consumers via Instagram increase brand awareness. This research uses descriptive qualitative methods, collecting data through observation, interviews and documentation. In this research, IMC (Integrated Marketing Communication) theory is used. The research results show that MS Glow Distributor Palembang carries out a marketing communication strategy in building brand awareness, there are marketing communication elements, namely: (1) MS Glow Distributor Palembang carries out promotions using five promotion mixes in integrated marketing communications, namely Advertising, Sales Promotion (Sales). Promotion), Direct Marketing, Personal Selling, Public Relations. (2) Supporting factors for MS Glow in increasing brand awareness, namely: endorsing, providing testimonials on product use, and the role of reels and live Instagram features. Meanwhile, the inhibiting factor for MS Glow Palembang distributors in increasing brand awareness is the large number of people who sell products below normal prices